Phase I/II study of GM-CSF DNA as an adjuvant for a multipeptide cancer vaccine in patients with advanced melanoma - Perales, Miguel-Angel (2008)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) enhances immune responses by inducing dendritic cell proliferation, maturation, and migration and B and T lymphocyte expansion and differentiation. The potency of DNA vaccines can be enhanced by the addition of DNA encoding cytokines, acting as molecular adjuvants. We conducted a phase I/II trial of human GM-CSF DNA in conjunction with a multipeptide vaccine (gp100 and tyrosinase) in stage III/IV melanoma patients. Nineteen human leukocyte antigen (HLA)-A*0201(+) patients were treated. Three dose levels were studied: 100, 400, and 800 mcg DNA/injection, administered subcutaneously (SQ) every month with 500 mcg of each peptide. In the dose-ranging study, 3 patients were treated at each dose level. The remaining patients were then treated at the highest dose. Most toxicities were grade 1 injection site reactions. Eight patients (42%) developed CD8+ T-cell responses, defined by a ≥3 SD increase in baseline reactivity to tyrosinase or gp100 peptide in tetramer or intracellular cytokine staining assays. There was no relationship between dose and T-cell response. Responding T cells had an effector memory cell phenotype. Polyfunctional T cells were also demonstrated. At a median of 31 months follow-up, median survival has not been reached. Human GM-CSF DNA was found to be a safe adjuvant.